Minimally Invasive Surgery and Sentinel Lymph Node Biopsy – a Modern Standart of Uterine Confined Endometrial Cancer Treatment: Reviewing Literature and Presenting the National Cancer Institute Experience - Čiurlienė, Rūta; Žilovič, Diana; Romeikienė, Karolina Eva; Šidlovska, Evelina (Lietuvos chirurgija, 2020)
Objectives. To find out sentinel lymph node detection rate of low-risk endometrial cancer patients. To compare postoperative complications rate, lenght of a surgery, lenght of hospital stay and sensitivity of detecting lymph node metastasis between minimally invasive surgery with sentinel lymph node biopsy and abdominal surgery with systemic pelvic lymphadenectomy. Methods. Retrospective analysis of low-risk endometrial cancer patients, treated in National Cancer Institute (n = 103) history cases from 2018 10 untill 2019 12. I group – laparoscopic hysterectomy with sentinel lymph node biopsy (n = 35); II group – abdominal hysterectomy with systemic pelvic lymphadenectomy (n = 68). Both groups were homogeneous according to clinicopathological features. Results. Sentinel lymph node were detected in 97.1% cases. Sentinel lymph nodes in both sides were detected in 85.7% cases. Metastasis in regional lymph nodes were detected in 2 cases (5.7%) in group I and none group II. Postoperative complications rate in group I were 3.8% and 13% in group II. Conclusions. There are significantly less postoperative complications in endoscopic surgery with sentinel node biopsy for low-risk endometrial cancer treatment, also this method is more accurate in surgical staging in National Cancer Institute.